Analisis Kemampuan Membaca dan Menulis Al-Qur’an Mahasiswa PAI dalam Konteks Persiapan Masa Depan Sebagai Pengajar Al-Quran Bagi Peserta Didik - Ayu, Yessilya (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2024)
This research reflects its relevance to the issue of Islamic religious education. This research will make an important contribution to improving Islamic religious education and the preparation of Al-Quran teachers in the future. This research aims to analyze PAI students' ability to read and write the Quran in the context of their future preparation as teachers of the Koran for students. To answer the research questions above, the author used a qualitative research method with a literature study approach. This article shows that the better PAI students' ability to read and write the Quran, the better they will be at guiding students in reading and writing the Quran. This thesis statement is the same as Rici Ratnasari (2020) and Syahrul Mahyuddin Siregar (2021) who state that teachers who have the ability to read and write the Quran well and correctly will be able to produce students who have the ability to read and write the Quran well and right too. And those who reject this thesis statement are Alfiyatus Sholihah (2023) who states that in learning to read and write the Quran, educators need to prepare various components, namely strategies, techniques and certain learning methods so that learning is effective and efficient.